Evaluating the Diagnostic Accuracy of High-Resolution Computed Tomography in Detecting COVID-19: A Comparative Study Using Polymerase Chain Reaction as the Gold Standard: Diagnostic Accuracy in Detecting COVID-19 - Saleem, Rida; Khan, Shandana; Nowsherwan, .; Shuaib, Syed Luqman; Syed, Rabia; Sattar, Mamoona (Pakistan Journal of Health Sciences, 2025)
Pakistan has faced three waves of COVID-19, each intensifying the strain on diagnostic resources. Delayed diagnoses during these waves hindered timely treatment and contributed to disease transmission. Objective: To evaluate the diagnostic accuracy of High-Resolution Computed Tomography (HRCT) in detecting COVID-19, using Polymerase Chain Reaction (PCR) as the gold standard. Methods: A cross-sectional study was conducted from November 26, 2021, to May 26, 2022, at the Department of Radiology, Northwest General Hospital & Research Centre, Peshawar. The study included 234 clinically suspected COVID-19 patients, aged 20–60 years, of both genders. Chest CT scans were performed, and results were compared with PCR. Data were analyzed using SPSS version 20, with p<0.05 considered significant. Results: Of the 234 patients, 133 tested positive for COVID-19 via PCR, while 101 were negative. HRCT demonstrated an overall accuracy of 73.9%, sensitivity of 72.9%, specificity of 75.2%, positive predictive value of 79.5%, and negative predictive value of 67.8%. Chi-square analysis revealed significant correlations of HRCT accuracy with BMI (p=0.004) and illness duration (p=0.010) but not with age (p=0.956) or gender (p=0.113). Conclusions: HRCT shows reasonable sensitivity, specificity, and overall accuracy as a diagnostic tool for COVID-19. Its performance improves in women, those with higher BMI, and longer illness duration but should not replace PCR testing due to its modest negative predictive value.